Abnormal Temporal Coupling of Tactile Perception and Motor Action in Parkinson’s Disease - Conte, Antonella; Belvisi, Daniele; Tartaglia, Matteo; Cortese, Francesca Natalia; Baione, Viola; Battista, Emanuele; Zhu, Xiao Y.; Fabbrini, Giovanni; Berardelli, Alfredo (Frontiers in Neurology, 2017)
Evidence shows altered somatosensory temporal discrimination threshold in Parkinson’s disease in comparison to normal subjects. In healthy subjects movement execution modulates somatosensory temporal discrimination threshold values through mechanisms of sensory gating. We investigated whether somatosensory temporal discrimination threshold modulation during movement execution in patients with Parkinson’s disease differs from that in healthy subjects. In twenty-four patients with Parkinson’s disease and twenty healthy subjects we tested somatosensory temporal discrimination threshold at baseline and during index-finger abductions (at movement onset “0 ms”, 100 ms and 200 ms thereafter). We also recorded kinematic features of index finger abductions. Fifteen out of the twenty-four patients were also tested ON medication. In healthy subjects somatosensory temporal discrimination threshold increased significantly at 0 ms, 100 ms and 200 ms after movement onset, whereas in patients with Parkinson’s disease in OFF therapy, it increased significantly at 0 ms and 100 ms but returned to baseline values at 200 ms. When patients were tested ON therapy, somatosensory temporal discrimination threshold during index finger abductions increased significantly, with a time course similar to that of healthy subjects. Differently from healthy subjects, in patients with Parkinson’s disease the mean velocity of the finger abductions decreased according to the time lapse between movement onset and the delivery of the paired electrical stimuli for testing somatosensory temporal discrimination. In conclusion patients with Parkinson’s disease show abnormalities in the temporal coupling between tactile information and motor outflow. Our study provides first evidence that altered temporal processing of sensory information play a role in the pathophysiology of motor symptoms in Parkinson’s disease.